Peran Wanita Karir Dalam Pendidikan Anak Menurut Hadits Dan Konstitusi - Ramania, Restu; Arifin, Tajul (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
This journal aims to understand the role of career women in children's education based on hadith and constitutional perspectives. The method used is literature study, namely data collection by finding sources from various books, reviewing, and processing them. The results showed that the hadith and the constitution have similar views in viewing the role of career women in children's education. The hadith emphasizes the mother's responsibility in caring for and educating children, but does not prohibit women from working. The constitution guarantees women's right to work and education, and ensures that children's rights to education and care are fulfilled. In conclusion, the role of career women in children's education is not contrary to Islamic teachings and positive law in Indonesia. Career women can play an active role in educating children while still paying attention to the needs and rights of children.